Pre-treatment loss to follow-up in adults with pulmonary TB in Kenya - M. N. Mulaku; E. Ochodo; T. Young; K. R. Steingart (Public Health Action, 2024)
SETTING: County referral hospital in western Kenya. OBJECTIVES: To ascertain the proportion of pre-treatment loss to follow-up (PTLFU) and associated patient factors in adults with pulmonary TB (PTB) in western Kenya. DESIGN: A retrospective data review of laboratory and treatment registers for adults with bacteriologically confirmed PTB between January 2018 to December 2021. We defined PTLFU as failure to initiate treatment within 14 days of diagnosis. We used multivariable logistic regression modelling to identify patient factors associated with PTLFU. RESULTS: Of 476 patients with PTB, 67.2% were male; the mean age was 36.1 years; 37.0% were HIV-positive; 5.7% had a history of anti-TB treatment; 40.6% were not traceable in the treatment register; 202 (42.4%, 95% CI 38.1–46.9) experienced PTLFU. Age ≥55 years (aOR 2.6, 95% CI 1.0–6.7) and providing only an address (aOR 34.2, 95% CI 18.7–62.5) or only a telephone contact number (aOR 22.3, 95% CI 3.5–141.1) were associated with PTLFU. Sex, HIV status, history of anti-TB treatment and place of residence were not associated with PTLFU. CONCLUSION: PTLFU contributes markedly to TB patient losses in western Kenya. Strengthening systems for documenting patient information and actively monitoring PTLFU are crucial for attrition reduction.